2020
DOI: 10.1186/s13018-020-1564-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stability study of three techniques used in the fixation of transverse and oblique metaphyseal-diaphyseal junction fractures of the distal humerus in children: a finite element analysis

Abstract: Background: Management of distal humerus metaphyseal-diaphyseal junction (MDJ) region fractures can be very challenging mainly because of the higher location and characteristics of the fracture lines. Loss of reduction is relatively higher in MDJ fractures treated with classical supracondylar humerus fractures (SHFs) fixation techniques. Methods: Three different fracture patterns including transverse, medial oblique and lateral oblique fractures were computationally simulated in the coronal plane in the distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Nevertheless, no clear preference was revealed by the survey about pin configuration as crossed pins (33.7%) and two divergent lateral (23.9%) pins were mostly done. This result reflects the uncertainty of the literature with several biomechanical [33][34][35][36] and clinical [37][38][39] studies reporting the superiority of a pin configuration over the others. Crossed pinning has been found to be the most stable configuration in different fracture patterns, [33][34][35][36] especially when three k-wire (two lateral and one medial) are used; 33 however, a recent metanalysis 39 reported 4.9% of iatrogenic ulnar nerve injury in crossed pinning, but the performance of safe procedure for the medial pin 40 can significantly reduce the risk of injuring the nerve.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, no clear preference was revealed by the survey about pin configuration as crossed pins (33.7%) and two divergent lateral (23.9%) pins were mostly done. This result reflects the uncertainty of the literature with several biomechanical [33][34][35][36] and clinical [37][38][39] studies reporting the superiority of a pin configuration over the others. Crossed pinning has been found to be the most stable configuration in different fracture patterns, [33][34][35][36] especially when three k-wire (two lateral and one medial) are used; 33 however, a recent metanalysis 39 reported 4.9% of iatrogenic ulnar nerve injury in crossed pinning, but the performance of safe procedure for the medial pin 40 can significantly reduce the risk of injuring the nerve.…”
Section: Discussionmentioning
confidence: 77%
“…This result reflects the uncertainty of the literature with several biomechanical [33][34][35][36] and clinical [37][38][39] studies reporting the superiority of a pin configuration over the others. Crossed pinning has been found to be the most stable configuration in different fracture patterns, [33][34][35][36] especially when three k-wire (two lateral and one medial) are used; 33 however, a recent metanalysis 39 reported 4.9% of iatrogenic ulnar nerve injury in crossed pinning, but the performance of safe procedure for the medial pin 40 can significantly reduce the risk of injuring the nerve. 37,38 To avoid ulnar nerve injury, lateral pinning is the preferred fixation technique by 50% of respondents; in particular, most surgeons use two lateral pins (38.6%) and the remaining three (11.4%).…”
Section: Discussionmentioning
confidence: 77%
“…In this context, we believe that modeling and simulation techniques developed for engineering purposes would be helpful. Liu et al[ 6 ] compared fixation methods used in SHFs through a simulation program (3D FEA) and found cross K-wiring to be effective, particularly in transverse SHFs, as it increased resistance against rotation, flexion, and varus loading. They also compared their findings with other relevant studies and concluded that their findings were compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The most accepted one is two lateral and one medial K-wires crossing the fracture line. [ 5 , 6 ] However, the importance of the angle between the fracture and the K-wires in SHFs is still a question that needs to be answered.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic stable intramedullary nailing for high supracondylar MDJ fractures have been reported due to the difficulty in achieving bicortical fixation with Kirschner wires (K-wires) (5,(9)(10)(11). Lateral external fixator, another surgical option, has also demonstrated superior outcome for oblique or comminuted fracture (6). The traditional percutaneous pinning for the pediatric supracondylar fracture should be modified based on more precise classification and diverse treatment methods, not just on the severity of displacement (4,8,9).…”
Section: Introductionmentioning
confidence: 99%